2013
DOI: 10.1007/s10753-013-9606-2
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9/Mig Mediates T cells Recruitment to Valvular Tissue Lesions of Chronic Rheumatic Heart Disease Patients

Abstract: Rheumatic fever (RF) is an autoimmune disease triggered by Streptococcus pyogenes infection frequently observed in infants from developing countries. Rheumatic heart disease (RHD), the major sequel of RF, leads to chronic inflammation of the myocardium and valvular tissue. T cells are the main population infiltrating cardiac lesions; however, the chemokines that orchestrate their recruitment are not clearly defined. Here, we investigated the expression of chemokines and chemokine receptors in cardiac tissue bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Repeated GAS throat (and possibly skin) infections are important in generating molecular mimicry, breaking immune tolerance and inducing epitope spreading, which leads to recognition of more epitopes in cardiac myosin and potentially other heart proteins. For example, epitopes shared among different streptococcal emm types in the B or C repeat regions of the streptococcal M proteins might prime the immune system against the heart during repeated streptococcal exposure and might eventually lead to RHD in susceptible individuals 87,111–113 . The A repeat regions of the GAS M proteins that are responsible for the type-specific protection against infection from each serotype are not shared with other M types and are not cross-reactive.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated GAS throat (and possibly skin) infections are important in generating molecular mimicry, breaking immune tolerance and inducing epitope spreading, which leads to recognition of more epitopes in cardiac myosin and potentially other heart proteins. For example, epitopes shared among different streptococcal emm types in the B or C repeat regions of the streptococcal M proteins might prime the immune system against the heart during repeated streptococcal exposure and might eventually lead to RHD in susceptible individuals 87,111–113 . The A repeat regions of the GAS M proteins that are responsible for the type-specific protection against infection from each serotype are not shared with other M types and are not cross-reactive.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…These include integrin α4β1 (also known as VLA4), intracellular adhesion molecule 1 (ICAM1), P-selectin, CC-chemokine ligand 3 (CCL3; also known as MIP1α), CCL1 (also known as I309) and CXC-chemokine ligand 9 (CXCL9; also known as MIG) 85,113 . The autoimmune reaction in the valves is associated with elevated levels of heart tissue proteins vimentin and lumican and elevated apolipoprotein A1 levels, whereas collagen VI, haptoglobin-related protein, prolargin, biglycan and cartilage oligomeric matrix protein are reduced 125 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…S. pyogenes -reactive T cells infiltrate both the myocardium and valvular tissue through specific integrins (VCAM, ICAM) and chemokines (CCL1/I-309, CXCL3/MIP1α, CXCL9/Mig) (16, 17). Once in the myocardium, T cells recognized cardiac myosin.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we verified that ICAM, another integrin, was also upregulated, in addition to P-selectin and several chemokines and their receptors. Among the chemokines, CCL3/MIP1α gene expression was up regulated in the myocardium, while CCL1/I-309 and CXCL9/Mig were highly expressed in the valvular tissue of RHD patients (17). An in vitro assay demonstrated that valvular lesions infiltrating T cells migrated mainly toward a CXCL9/Mig gradient, suggesting that specific chemokines can mediated both the CD4 + and CD8 + T cell recruitment to the site of inflammation in the heart (17).…”
Section: Heart Valve Chronic Inflammationmentioning
confidence: 99%
“…Através de ensaio de migração celular frente a diversas quimiocinas foi mostrado que o perfil dos linfócitos T que migravam para o coração apresentava fenótipo de memória (CD4 + CD45RO + ) em resposta principalmente a CXCL9/Mig (Faé et al, 2013).…”
Section: Aspectos Epidemiológicos Da Febre Reumática Eunclassified